Hexactinellid Sponge Reefs on the Canadian Continental Shelf: A Unique "Living Fossil" - Conway, Kim; Krautter, Manfred; Barrie, J.; Neuweiler, Matthias (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2001)
Summary Globally unique hexactinellid (siliceous) sponge reefs, found in deep (200 m), glacially scoured troughs of the western Canadian continental shelf, have been explored by a manned submersible. Submersible observations and geophysicaldata allow examination of the physical and biological processes that have shaped the sponge reefs, which began to form about 9 thousand years (k.y.) ago. The mounds (bioherms) and sheet-like accumulations (biostromes) cover a low-angle, non-depositional, iceberg-scoured seafloor, relict since the déglaciation of the region. Biohermal structures are up to 19 m in height, and are covered with hexactinosan sponges up to 1.5 m tall, creating abenthic habitat that discontinously covers roughly 700 km2. Similar to extinctsiliceous sponge reefs, mud mounds, and reef mounds that were widespread during the Mesozoic, the modern reefs are like a"living fossil" and provide a unique modern analogue. Fishing activities, especially trawling or bottom dragging, have damaged the slow-growing reefs insome areas.